107 Short term neuropsychiatric outcomes of STN – DBS using directional vs conven- tional ring mode stimulation. Issue 9 (12th August 2022) - Hammersley, Beth; Bonello, Michael; Fahad, Salam; Costa, Antonio Da; Mullin, Jenny; Farah, Jibril; Alusi, Sundus
Abstract : Achieving the best outcome from STN stimulation for the treatment of Parkinson's disease depends on ideal electrode placement and optimum stimulation settings. Motor symptoms are known to respond well to stimulation of the dorsolateral nucleus of the subthalamus and avoidance of tissue activation of the surrounding structures that may give rise to unwanted side effects including slurred speech, gait problems and neuropsychiatric symptoms. The recent development of multidirectional stimulation systems has enabled electrical current steering to activate the desired tissue areas in order to achieve effective neuromodulation. In this audit of 16 patients who underwent STN-DBS, we looked at the short-term neuropsychiatric outcomes in patients in whom current steering was deployed to achieve the best motor control to those in whom control was achieved by conventional ring mode stimulation. The patients' symptoms were assessed at baseline and at 12 months using validated scales for anxiety, depression, apathy, and impulsivity. There was no statistical difference in the neuro-psychiatric outcomes between the two groups. However, the number of patients in this study was small and larger studies for longer periods are required to evaluate the potential benefit of this new development in minimising the neuropsychiatric complications of this treatment.